2008
DOI: 10.1001/archpedi.162.10.969
|View full text |Cite
|
Sign up to set email alerts
|

Missed Diagnosis of Critical Congenital Heart Disease

Abstract: Up to 30 infants per year died of a missed or possibly late diagnosis of CCHD in California. Most deaths due to a missed diagnosis were from HLHS and coarctation of the aorta. Because the median age at death was younger than 2 weeks, a careful cardiovascular evaluation for left heart obstructive CHD should be performed during the first postdischarge visit to a pediatrician's office at 3 to 5 days of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
157
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(168 citation statements)
references
References 37 publications
5
157
1
5
Order By: Relevance
“…More than 50% of CCHD deaths (up to 30 infants a year) could be attributed to late or missed diagnosis in the neonatal period in the state of California alone [7]. Evidence presented in the Chang study and others [8] demonstrated that additional methods of detection for CCHD, aside from prenatal ultrasound and physical examination of the neonate, were needed.…”
Section: Early Studies and 2009 Scientific Statementmentioning
confidence: 98%
“…More than 50% of CCHD deaths (up to 30 infants a year) could be attributed to late or missed diagnosis in the neonatal period in the state of California alone [7]. Evidence presented in the Chang study and others [8] demonstrated that additional methods of detection for CCHD, aside from prenatal ultrasound and physical examination of the neonate, were needed.…”
Section: Early Studies and 2009 Scientific Statementmentioning
confidence: 98%
“…[1][2][3][4] Newborn infants with CoA may be initially asymptomatic, but they will rapidly deteriorate after constriction of the arterial duct and risk death if not diagnosed in time to reverse the situation with prostaglandin E1 (PGE1). In a previous study, we found that newborns with critical congenital heart defects (CCHDs) were increasingly being discharged undiagnosed from the maternity ward in parallel with shorter postnatal stays and that aortic arch obstruction was the most frequently missed cardiac defect.…”
mentioning
confidence: 99%
“…3,5,6 Several also incorporate a measure of severity, including a requirement that surgery, catheterization, or death occur within a specified time period, ranging from the first few weeks to the first year of life. [7][8][9] Although delayed diagnosis of CCHDs has been associated with serious complications, including seizure, cardiac arrest, and death, 7,10,11 few studies have examined temporal trends or factors associated with delayed diagnosis. Previous studies of late-detected CCHD differ in case definition and study methodology, but most have reported prevalence rates of ∼20% to 30%.…”
mentioning
confidence: 99%
“…Previous studies of late-detected CCHD differ in case definition and study methodology, but most have reported prevalence rates of ∼20% to 30%. 6,[11][12][13] Factors that have been associated with late diagnosis include certain CCHD types, 6,8,9,12 nontertiary hospital nursery, 12 and absence of extracardiac defects. 6 The Secretary of Health and Human Services has recommended routine screening of newborns for CCHD with pulse oximetry, because earlier diagnosis may lead to better outcomes.…”
mentioning
confidence: 99%